2017
DOI: 10.21608/edj.2017.74541
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Omega-3 Fatty Acids Combined With Initial Periodontal Therapy on Salivary Visfatin and TNF-Α Levels in Chronic Periodontitis Patients

Abstract: Recent investigations have demonstrated the positive therapeutic effects of omega-3 polyunsaturated fatty acids (PUFAs) on several chronic inflammatory diseases such as rheumatoid arthritis, chronic inflammatory bowel diseases and periodontitis. The objective of the present study was to evaluate the impact of omega-3 PUFAs in conjunction with initial periodontal therapy (IPT) on periodontal clinical parameters and salivary markers in patients with chronic periodontitis. Thirty four systemically healthy individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The following criteria led to exclusion: Screening of titles and abstracts by both independent reviewers (LMM and FBP) resulted in retention of the same 28 articles (Figure 2). After reading all the articles thoroughly, additional exclusions were made due to the following criteria: The diagnosis of the patients in the included studies varied from moderate/severe chronic [41], untreated advanced chronic [43], chronic [38,42], generalized chronic [39,40] to stage II/III periodontitis [44] and stage III/IV periodontitis [45] according to the most recent classification [46]. Six out of eight studies presented detailed criteria for patient selection.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The following criteria led to exclusion: Screening of titles and abstracts by both independent reviewers (LMM and FBP) resulted in retention of the same 28 articles (Figure 2). After reading all the articles thoroughly, additional exclusions were made due to the following criteria: The diagnosis of the patients in the included studies varied from moderate/severe chronic [41], untreated advanced chronic [43], chronic [38,42], generalized chronic [39,40] to stage II/III periodontitis [44] and stage III/IV periodontitis [45] according to the most recent classification [46]. Six out of eight studies presented detailed criteria for patient selection.…”
Section: Resultsmentioning
confidence: 99%
“…The number of teeth, as far as presented, varied greatly among studies. Two studies reported the number of teeth examined [42,43]. Four authors did not report the number of teeth examined but defined the inclusion criteria based on the minimum number of teeth present: at least 6 [40], 15 [38], ≥18 [45] and 20 [39].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations